National Geographic essential visual history of the Bible (Washington, D.C : National Geographic Society, 2008)
An illustrated history of the Bible provides detailed coverage of the Old and New Testaments, from the patriarchs to the epistles of Paul, and includes timelines and informational sidebars
The Old Testament -- The New Testament
Includes index.
Keywords: BIBLE -- DICTIONARY